Data Mining Approach to Analyze the Road Accidents in India - Usha Rani, N; Vanaja, T (International Journal of Computer Sciences and Engineering, 2025)
The accident is an unplanned incident which leads to injury to people, damage to a plant, machinery or some other loss. The goal of this paper is an analysis of road accidents at country level and statewide of India. The analysis shows that accidental fatalities and injuries changes according to age, gender, month and time. Analysis of road accidents plays an important role in the transportation system. Road traffic injuries and fatalities are common in nature it would be impractical to predict one-to-one relationship among the safety measures in road accidents, injuries, and fatalities. Road safety is an important concern for both national and international level. Data mining tools and techniques are used to predict accident-prone locations. For every four minutes, one death is occurred due to road mishap in India. The crucial thing is an analysis of road accident data is its heterogeneousness. The relationship between road surface conditions, road type, severity, light conditions, etc. are investigated.